ANALISIS PENGARUH DAYA TARIK WISATA BERBASIS MASYARAKAT TERHADAP MINAT BERKUNJUNG DI KAMPUNG KERANGGAN - Yonatan, Rizki; Sarudin, Rendy (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to assess the effect of the attractiveness of community-based tourism on visiting interest in the Keranggan Tourism Village. The quantitative method was used by random sampling on 100 respondents who had visited the village at least twice. Data were analyzed using SPSS version 27 with an online questionnaire. The results show that community-based tourism (X) has a high average of 3.88, while interest in visiting (Y) has the highest average of 4.04. R square of 66.7% indicates that interest in visiting is influenced by community-based tourism, the rest by other factors. It is recommended that the manager maintain and improve community-based tourism so that interest in visiting the Keranggan Tourism Village will increase.